Oil palm (Elaeis guineensis Jacq.) shaded model at immature stage II and application of arbuscular mycorrhizal fungi (AMF) on growth and yields of soybean (Glycine max (L.) Merrill - Suherman, Cucu; Indri, F; Santi Rosniawaty; Mochammad Arief (Penerbit Universiti Kebangsaan Malaysia, 2022)
The practice of intercropping soybeans among oil palm trees is an approach used to optimize plantation land. Oil palm (OP) at the second immature stage (IS-2) or the age of 2 years provides shade of around 40%. This research aimed to observe soybean growth and yields under shade conditions close to those of oil palm shading conditions at IS-2 and to determine the optimal dosage of Arbuscular Mycorrhizal Fungi (AMF) to apply to the soybeans. The shade intensity treatment used artificial shading nets close to actual shade intensity in OP plantation, i.e., 40% shading. The experiment was conducted at the Experimental Station, Faculty of Agriculture, Universitas Padjadjaran, from October 2019 to January 2020. The experimental design used was a split-plot design with shade intensity as the main plots (0 and 40%) and AMF dosage as subplots, consisting of six treatments of 0, 2, 4, 6, 8, and 10 g/plant, with each treatment repeated four times. The results showed that at 10 weeks after planting, the interaction effect of 40% shade intensity with a dosage of 10 g AMF per plant resulted in the highest chlorophyll index. Independently, the AMF dosage of 10 g per plant produced the maximum plant height, number of productive branches, dry weight of plants, and number of seeds per pod.